2000
DOI: 10.1055/s-2000-8410
|View full text |Cite
|
Sign up to set email alerts
|

Biportal Endoscopic Removal of a Primary Intraventricular Hematoma: Case Report

Abstract: Primary intraventricular hematomas account for approximately 6% of all intracerebral hematomas. If the clot blocks cerebrospinal fluid (CSF) pathways, surgical intervention, which may be of different types, can be life-saving. In the case reported here, after careful preoperative planning the use of two rigid endoscopes permitted the removal of most of the intraventricular clot and restoration of CSF circulation by creation of a 3rd ventriculostomy within the same procedure and no later treatment was necessary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 16 publications
0
24
0
6
Order By: Relevance
“…11 Our results confirm previous reports showing positive outcomes in patients with IVH treated with neuroendoscopic approach. [12][13][14] In all cases, efficient removal of intraventricular clots was rapidly achieved. However, in 2 of these reports, use of the rigid endoscope required either a cumbersome biportal approach 12 or an ultrasonic aspirator 13 with a high risk (20%) of postoperative rebleeding.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…11 Our results confirm previous reports showing positive outcomes in patients with IVH treated with neuroendoscopic approach. [12][13][14] In all cases, efficient removal of intraventricular clots was rapidly achieved. However, in 2 of these reports, use of the rigid endoscope required either a cumbersome biportal approach 12 or an ultrasonic aspirator 13 with a high risk (20%) of postoperative rebleeding.…”
Section: Discussionmentioning
confidence: 98%
“…[12][13][14] In all cases, efficient removal of intraventricular clots was rapidly achieved. However, in 2 of these reports, use of the rigid endoscope required either a cumbersome biportal approach 12 or an ultrasonic aspirator 13 with a high risk (20%) of postoperative rebleeding. The latter procedure was applied to newborns, 14 a patient category hardly comparable to ours.…”
Section: Discussionmentioning
confidence: 98%
“…8,16,25,36,37,51 In all cases, efficient removal of intraventricular clots was rapidly achieved. However, in 2 of these reports, use of a rigid endoscope required either a cumbersome biportal approach 17 or an ultrasonic aspirator, 38 with a high risk (20%) of postoperative rebleeding. The use of a flexible instrument and the freehand technique, albeit offering a narrower operating channel, allows more complete cleansing of the third ventricle and navigation down to the fourth ventricle through the aqueduct.…”
Section: Endoscopic Aspirationmentioning
confidence: 99%
“…Many studies have demonstrated the independent effect of IVH on mortality. [16][17][18][19][20] Neuroendoscopy may offer some advantages over more traditional surgical approaches such as EVD placement and intraventricular fibrinolysis and should be considered the gold-standard approach, especially when dealing with elderly patients in poor general health.…”
mentioning
confidence: 99%
See 1 more Smart Citation